Native lead in the rocks of deep-lying petroliferous complexes - Lukin, O.Yu.; Shestopalov, V.M.; Lukin, Ya.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
The presence of native-lead aggregated particles within the secondary pores (cavities) and (micro) fractures is established as a result of the electronic-microscope (with energy dispersion) analysis of deep-lying oil-and-gas reservoir rocks. Their granular (sinter-collomorphic), lamellar and microinjection morphologic types are distinguished Native lead particles (similar to other native metals) may be considered as the tracks of superdeep (mantle) reduced fluids. An additional point to emphasize is connected with its high plasticity owing which the lead particles may serve as tectonophysics indicators of a microstress distribution within deep-lying reservoir rocks.